Support System Kepatuhan Dialisis Pasien Penyakit Ginjal Kronik: Path Analisis Berdasarkan Teori Health Promotion Model - Vini Anjelia Pattinaja; Eko Winarto; Yunani Yunani (Poltekkes Kemenkes Padang, 2024)
Chronic Kidney Disease (CKD) is a condition characterized by end-stage renal failure caused by various factors, marked by a decline in the glomerular filtration rate (GFR) below 60 ml/min/1.73 m² for more than five months, necessitating lifelong renal replacement therapy through dialysis. This study aims to identify the support systems that influence dialysis adherence among CKD patients. Using a reciprocal analysis design with path coefficients, the study involved 102 patients undergoing hemodialysis at RS X Jakarta. Multivariate analysis was conducted using SPSS, and path analysis was performed with Smart PLS 3. The results indicate that family support has a significant positive effect on dialysis adherence (O = 2.279; t-statistic 3.019; p = 0.003). Additionally, peer support, through perceptions of dialysis adherence, showed a significant indirect effect (O = 1.979; t-statistic 0.128; p = 0.048). The coefficient of determination for the support system variable was 11% (0.110), indicating that 11% of the variation in dialysis adherence is influenced by the support system. In conclusion, there is a significant relationship along with both direct and indirect effects of support system variables on dialysis adherence among chronic kidney disease patients.